2020
DOI: 10.1016/j.fertnstert.2019.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative nonhormonal pharmacological interventions for bleeding reduction during open and minimally invasive myomectomy: a systematic review and network meta-analysis

Abstract: Objective: To synthesize evidence on the most effective pharmacological interventions for bleeding reduction during open and minimally invasive myomectomy. Design: Systematic review and network meta-analysis of randomized controlled trials (RCTs). Setting: Not applicable. Patients: Trials assessing efficacy of pharmacological interventions during different types of myomectomy. Interventions: Misoprostol, oxytocin, vasopressin, tranexamic acid (TXA), epinephrine, or ascorbic acid. Main Outcome Measures: Intraop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…The authors found that the operating time and the decrease in hemoglobin concentration were similar in both the study and control groups [99]. Samy et al (2020) studied anti-hemorrhagic agents during myomectomy and found that ascorbic acid and a combination of epinephrine plus bupivacaine were the least effective pharmacological options in this indication [100]. Interestingly, endometrial thinning was effectively treated with vitamins C and E in an infertile woman undergoing myomectomy.…”
Section: Vitamin C and Uterine Fibroidsmentioning
confidence: 96%
See 1 more Smart Citation
“…The authors found that the operating time and the decrease in hemoglobin concentration were similar in both the study and control groups [99]. Samy et al (2020) studied anti-hemorrhagic agents during myomectomy and found that ascorbic acid and a combination of epinephrine plus bupivacaine were the least effective pharmacological options in this indication [100]. Interestingly, endometrial thinning was effectively treated with vitamins C and E in an infertile woman undergoing myomectomy.…”
Section: Vitamin C and Uterine Fibroidsmentioning
confidence: 96%
“…Examples of using vitamin C and its analogs and derivatives are found in dermatology [198], and therefore some data could be referred to regarding this discussed matter. It ha been demonstrated that the use of vitamin C in the treatment of intraoperative bleeding was rather experimental and presented no considerable clinical effect [100].…”
Section: New Trends and Possible Future Role Of Vitamins In Uterine Fmentioning
confidence: 99%
“…However, operative hysteroscopy may be associated with complications such as uid overload, uterine perforation, and bleeding [8]. Several strategies have been used to facilitate the procedure and improve prognosis [9][10][11]. There is evidence on using gonadotropin agonists [12,13] and letrozole [14] as a preoperative intervention.…”
Section: Introductionmentioning
confidence: 99%
“…However, operative hysteroscopy may be associated with some complications such as fluid overload, bleeding, and uterine perforation [8]. Several strategies have been used to facilitate the procedure and improve the prognosis [9][10][11]. There is evidence on using gonadotropin agonists [12,13] and letrozole [14] as a preoperative intervention.…”
Section: Introductionmentioning
confidence: 99%